Count crowley volume 2 amateur midnight monster hunter ebook - Dastmalchian, David (Count Crowley, 2023)
Jerri Bartman never imagined herself dressed up like a ghoul, hosting the late-night creature feature in her small hometown of Beloit, Missouri. Of course, she never imagined that she might be an alcoholic… or the fact that monsters are real.Not only are these the sobering facts, but Jerri seems to be the only person capable of battling the growing threat of zombies, werewolves, and vampires spinning fake news into the world. Reluctantly embracing her mission as a monster hunter, Jerri will have to swallow her pride, lace up her combat boots, and figure out the real way to slay the stalking creatures of the night.Collects Count Crowley: Amateur Midnight Monster Hunter issues #1–#4.